2015
DOI: 10.1038/ncomms7137
|View full text |Cite
|
Sign up to set email alerts
|

Augmented AMPK activity inhibits cell migration by phosphorylating the novel substrate Pdlim5

Abstract: Augmented AMP-activated protein kinase (AMPK) activity inhibits cell migration, possibly contributing to the clinical benefits of chemical AMPK activators in preventing atherosclerosis, vascular remodelling and cancer metastasis. However, the underlying mechanisms remain largely unknown. Here we identify PDZ and LIM domain 5 (Pdlim5) as a novel AMPK substrate and show that it plays a critical role in the inhibition of cell migration. AMPK directly phosphorylates Pdlim5 at Ser177. Exogenous expression of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
98
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 43 publications
(67 reference statements)
4
98
0
Order By: Relevance
“…GAG is structurally similar to LPS and is involved in pathogenesis of inflammation through LPS signalling pathways (Simonaro et al, 2008). Numerous studies demonstrated that the AMPK activator AICAR enhances the phagocytic ability of macrophages via a variety of signalling events, and AMPK activation induces cytoskeletal reorganization (Bae et al, 2011;Yan et al, 2015). Consistent with earlier studies, our results showed that AICAR increased the phagocytic ability of macrophages.…”
Section: Discussionsupporting
confidence: 94%
“…GAG is structurally similar to LPS and is involved in pathogenesis of inflammation through LPS signalling pathways (Simonaro et al, 2008). Numerous studies demonstrated that the AMPK activator AICAR enhances the phagocytic ability of macrophages via a variety of signalling events, and AMPK activation induces cytoskeletal reorganization (Bae et al, 2011;Yan et al, 2015). Consistent with earlier studies, our results showed that AICAR increased the phagocytic ability of macrophages.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we validated the expression of genes at the core nodes of the circRNA-miRNA-mRNA regulatory network by qPCR. PDLIM5, which was upregulated in TDP cells, functions as an oncogene in cancer by promoting cell proliferation and migration [27,28]. Moreover, miR-328, which interacts with PDLIM5, has Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry been found downregulated in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AMPK inhibits cancer cell migration and EMT via both TGF-b-dependent and -independent mechanisms (Cufi et al, 2010;Xiao et al, 2010;Lim et al, 2012;Chou et al, 2014;Wang et al, 2014;Zhang et al, 2014;Thakur et al, 2015;Yan et al, 2015). With regard to AMPK regulation of the TGF-b signaling pathway, the mechanism is not clear.…”
Section: Introductionmentioning
confidence: 98%